Nanoscale Activation Energy Mapping and Leveraging for Accelerating Ferroelectric Domain Nucleation and Growth. (9th May 2022) - Nath, Ramesh; Polomoff, Nicholas A.; Song, Jingfeng; Moran, Thomas J.; Ramesh, Ramamoorthy; Huey, Bryan D.
Abstract: The dynamics of ferroelectric domain switching are directly mapped in a PbZr0.2 Ti0.8 O3 thin film using piezoresponse force microscopy. Employing the rastering tip as a poling electrode to locally apply a fixed bias near the coercive field, while simultaneously monitoring the evolving domain pattern during continuous imaging, the effectively independent switching dynamics for numerous domains are directly investigated. While areal poling follows the anticipated S‐curve, this is shown to be the collective outcome of linear terminal radial growth for an ensemble of independently nucleating domains. By repeating such spatially resolved measurements in the same region, but with progressively greater fields, nucleation sites and growth patterns are shown to clearly repeat. This reveals apparent defects which comparatively promote switching, and nucleation times and growth rates that accelerate exponentially. After analyzing and mapping the ratio of activation energies for nucleation to growth, a high density of nucleation sites can possibly be activated with higher poling fields—even if only at the start of a poling process—enabling faster and more efficient switching to be engineered as directly demonstrated. Abstract : Ferroelectric domain image sequences during polarization switching of PZT (PbZ0.2 Ti0.8 O3 ), each with stronger biases but all in one region, reveal distinct activation energies for defect mediated domain nucleation and linear radial growth. Collectively these yield conventional ferroelectric S‐curve switching, and confirm a route for accelerating switching using strong initial poling pulses to nucleate numerous fine domains which then efficiently propagate.